Local progression kinetics of geographic atrophy in age-related macular degeneration are associated with atrophy border morphology - Lindner, M; Kosanetzky, S; Pfau, M; Nadal, J; Gördt, LA; Schmitz-Valckenberg, S; Schmid, M; Holz, FG; Fleckenstein, M; FAM-Study Group (Association for Research in Vision and Ophthalmology, 2018)
Purpose: To assess the impact of distinct atrophy border characteristics based on spectral-domain optical coherence tomography (SD-OCT) imaging on local atrophy progression.